Scientific discussion of selected viruses including COVID-19 in hot springs (2020)
The objective of this study is to discuss selected viruses including COVID-19 and their potential elimination processes in hot springs. Studies in Colombia are limited and this scientific discussion provides necessary information regarding these viruses. This includes studies both in Colombia and international levels on the following subjects: i) the presence of viruses in hot springs, ii) the non- oxidative water treatment in hot springs, iii) the elimination strategies of viruses; and iv) the influence of COVID-19 in hot springs. The results of this discussion indicate that in order for thermal waters to guarantee the elimination of the viruses originating from faecal and nonfaecal derived, and the COVID-19 virus, a monitoring scheme is required to identify an effective disinfection of waters to control these pathogens.